Eco-sustainable biorefinery to the management of winery waste by integrating sequential ready-to-use pigments and bioenergy through advanced multi-step kinetic slow pyrolysis - Mussagy, Cassamo U.; de Souza Mesquita, Leonardo M.; Rostagno, Mauricio A.; Haddad, Felipe F. [UNESP]; dos Santos, Jean L. [UNESP]; Scarim, Cauê B. [UNESP]; Herculano, Rondinelli D.; Valette, Jérémy; Sangaré, Diakaridia (Elsevier, 2024)
This study aimed to design a sequential biorefinery from wine-making by-products for the obtaining value-added products, focusing on extracting natural pigments and the evaluation of bioenergy produced by remaining biomass from Carménère Grape Residues (CGR) through slow pyrolysis. To achieve these goals, solid-liquid extraction of pigments from CGR was performed using a reusable bio-based solvent. Concurrently, these pigments' antioxidant activity and toxicity were evaluated in embryo cells, exploring their potential applications in the cosmetic industry. Secondly, it focused on applying the residual colorless biomass derived from the initial extraction process. This involved the evaluation of kinetic triplet: apparent activation energy, pre-exponential factor, and reaction model. From these parameters, the thermodynamic properties (∆H, ∆G, and ∆S) were estimated. The results from the first step revealed the recovery of 18.21 mg/gCGR of total anthocyanin that exhibited robust antioxidant capabilities and compatibility with biological systems, indicating potential applications in the cosmetic industry. The pyrolysis of residual colorless biomass revealed a complex chemical structure with multiple stages of decomposition. The kinetic parameters, including activation energy and pre-exponential factor, indicated better energy yield than other biomass, highlighting the potential for bioenergy production. The difference between activation energy and standard enthalpy of the reaction was less than 5.72 kJ/mol, indicating a favorable exothermic reaction and the feasibility of the energetic process. This study provides insights into the dual benefits of utilizing CGR for pigments recovering and bioenergy, contributing to sustainable practices towards a circular economy model.
Keywords: Biorefinery; Carménère; Grape; Pigments; Pyrolysis; Residues